Associations between positive and negative social media experiences and sleep disturbance among young adults - Rzewnicki, Daniel I. (Sleep Health, 2020)
OBJECTIVES: We sought to examine the association of positive and negative experiences using social media (SM) and sleep disturbance in a national survey of U.S. young adults. METHODS: Experiences using social media were assessed with 2 items asking participants about the percentage of time using SM that involved a negative/positive experience that they were personally involved in. Sleep disturbance was assessed using the validated PROMIS 4-item short form. Ordinal logistic regression was used to examine associations between positive and negative SM experiences and high sleep disturbance, while controlling for relevant covariates. RESULTS: Although reporting high levels of negative experiences was significantly associated with greater odds of high sleep disturbance (AOR = 1.49, 95% CI = 1.18–1.89), reporting high levels of positive experiences was not associated with sleep disturbance. CONCLUSIONS: These findings suggest that more robust examinations of negative SM experiences—especially as they relate to sleep disturbance—may be warranted.